Analisis Kebijakan Dispensasi Kawin di Indonesia - Siswanto, Cecep Tedy (Jurnal Hukum Caraka Justitia, 2025)
This study aims to examine and analyze in depth the marriage dispensation policy, which can be one of the factors in the occurrence of early marriage or child marriage in Indonesia. This research is a normative juridical research with a legislative approach and a conceptual approach. The main data source in this study is secondary data, consisting of primary legal materials and secondary legal materials. The results of the study show that changing the minimum age of marriage to 19 years does strengthen child protection. However, the opportunity for dispensation still weakens the effectiveness of these efforts. The conceptual problem in the definition of "very urgent reason" does not provide concrete parameters, causing ambiguity of norms that have the potential to weaken legal certainty, especially for children. There is a need to reformulate the concept of "very urgent reasons" by setting objective and measurable criteria. These parameters need to be described in the marriage dispensation policy in the form of technical guidelines or derivative regulations that are not only used by judges as a consistent reference in examining marriage dispensation applications but also as a reference for the community as applicants.